High-density artificial bone repair material and preparation method thereof

By activate collagen and secondary chemical crosslinking, a high-density collagen artificial bone repair material is formed, which solves the problems of slow degradation and insufficient density of existing bone repair materials, and achieves higher compressive strength and More matching new bone growth rate.

CN119424745APending Publication Date: 2025-02-14CHANGZHOU BONE-RENEWAL MEDICAL TECHNOLOGIES LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411482164.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing bone repair materials degrade slowly in the body, hindering the growth of new bones, and the solubility of collagen materials is limited, making it difficult to increase density, resulting in a degradation time faster than the speed of new bone formation.

Method used

By activating the collagen raw material, its solubility in the acidic solution is significantly improved, and combined with secondary chemical crosslinking treatment, a high-density collagen artificial bone repair material is formed.

Benefits of technology

It significantly improves the compressive strength and density of the material, extends the degradation time in the body, and makes it more suitable for the growth rate of new bone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119424745A_ABST
    Figure CN119424745A_ABST
Patent Text Reader

Abstract

The invention discloses a high-density artificial bone repair material and a preparation method thereof. A preparation method of an artificial bone repair material comprises the following steps: A, obtaining a mixed solution of collagen and a first acid solution, and heating or irradiating the mixed solution to activate collagen molecules; b, dissolving the activated collagen in a second acid solution to obtain a collagen acid solution, adding calcium phosphate powder, uniformly mixing, and adding a cross-linking agent to obtain slurry; and C, injecting the slurry into a mold, carrying out a cross-linking reaction, and demolding. The artificial bone repair material disclosed by the invention is relatively high in density, the degradation time of the artificial bone repair material implanted into a human body is prolonged, and the growth rate of a new bone is favorably matched.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-density artificial bone repair material and a preparation method thereof. Background Art

[0002] Existing bone repair materials are mainly hydroxyapatite, which shows certain biocompatibility after implantation in the body, but it degrades slowly in the body. Studies have shown that hydroxyapatite has no obvious change in the position of bone defects after being implanted in the body for several years, which hinders the growth of new bone; see reference 1: Dorozhkin SV, Epple M. Biological and medical significance of calcium phosphates. Angew. Chem. Int. Ed. 2002, 41: 3130-3146. Compared with hydroxyapatite, tricalcium phosphate material has better degradation performance and can form chemical bonds with bones after implantation in the body, but it still lacks sufficient biological activity and cannot further promote the formation of new bone. Some researchers have improved the bioactivity of calcium phosphate materials by compounding collagen molecules. Collagen is an important component of human bone and has excellent osteoinductivity, which can induce bone cell proliferation and differentiation; see reference 2: Jiang QS, Wang LRand et al. Canine ACL reconstruction with an injectable hydroxyapatite / collagen paste for accelerated healing of tendon-bone interface. Bioact. Mater. 2023, 20: 1-15.

[0003] However, the degradation time of collagen molecules in the body is generally short. Even the degradation time of bovine type I collagen with a higher molecular weight (about 300kDa) is difficult to exceed three months; see reference 3: Biological properties and in vivo degradation and absorption of collagen sponges. Chinese Journal of Tissue Engineering Research. 2014, 18: 34. The regeneration and repair time of bone defects generally takes more than 6 months. Increasing the density of collagen sponges can effectively prolong the degradation time of collagen sponges, but the solubility of collagen materials is limited. The solubility concentration of bovine type I collagen does not exceed 10mg / mL, resulting in low solid content of collagen after freeze-drying, making it difficult to increase density. Therefore, the sponge-like artificial bone products formed by using collagen composite calcium phosphate materials generally have a degradation time faster than the rate of new bone formation, which is difficult to be used in the filling and repair of bone defects. It is urgent to develop new high-density collagen artificial bone products. Summary of the invention

[0004] The purpose of the present invention is to provide a high-density artificial bone repair material and a preparation method thereof. The obtained artificial bone repair material has a high density and a prolonged degradation time after implantation in the human body, which is conducive to matching the growth rate of new bone.

[0005] The present invention adopts the following technical solution:

[0006] A method for preparing an artificial bone repair material, comprising:

[0007] A. obtaining a mixture of collagen and a first acid solution, and heating or irradiating the mixture to activate collagen molecules;

[0008] B. dissolving the activated collagen in the second acid solution to obtain a collagen acid solution, adding calcium phosphate powder, mixing evenly, and then adding a cross-linking agent to obtain a slurry;

[0009] C. Injecting the slurry into a mold, undergoing cross-linking reaction, and demoulding.

[0010] In a preferred embodiment, the preparation method further comprises the following step D:

[0011] D. Immersing the composite material in a crosslinking agent solution for secondary chemical crosslinking, washing the crosslinked composite material, drying and forming the composite material to obtain an artificial bone repair material.

[0012] In some preferred embodiments, in step A, the mixed solution is heated to 40-95°C for activation. More preferably, the heating temperature for activation is 42-60°C; further 42-50°C.

[0013] In some preferred embodiments, the mixed solution is activated by irradiating with gamma rays.

[0014] In some preferred embodiments, in step A, the concentration of the first acid solution is 0.2-10wt%, the first acid solution includes a hydrochloric acid solution or an acetic acid solution, and the mass percentage of collagen in the mixed solution is 8-20%. More preferably, the concentration of the first acid solution is 1-10wt%, further 1-5wt%. More preferably, the mass percentage of collagen in the mixed solution is 10-20%, further 15-20%.

[0015] More preferably, the heating activation time is 1-10 minutes. Optionally, the irradiation is performed using 8-45 kGy of Co 60 Gamma ray irradiation.

[0016] In a specific and preferred embodiment, the heating temperature for activation is 42-50° C., and the activation time is 1-10 minutes.

[0017] In some preferred embodiments, the collagen includes a combination of one or more selected from type I collagen, type II collagen and repeated collagen, and the weight average molecular weight of the collagen is 20,000-300,000 Da.

[0018] In some preferred embodiments, in step B, the mass ratio of collagen to calcium phosphate powder is 0.05-1, the mass percentage of activated collagen in the collagen acid solution is 5-10%, and the concentration of the cross-linking agent is 10-500 ppm. More preferably, the mass ratio of collagen to calcium phosphate powder is 0.1-1; further 0.2-0.5.

[0019] In some preferred embodiments, in step B, the concentration of the second acid solution is 0.2-10wt%, and the second acid solution includes a hydrochloric acid solution or an acetic acid solution; the calcium phosphate powder includes a combination of one or more selected from tricalcium phosphate, magnesium-containing tricalcium phosphate, hydroxyapatite and octacalcium phosphate; and the cross-linking agent includes genipin and / or glutaraldehyde.

[0020] In some more preferred embodiments, the calcium phosphate powder is tricalcium phosphate or tricalcium phosphate containing magnesium. In a specific and preferred embodiment, the calcium phosphate powder is tricalcium phosphate containing magnesium, and the mass percentage of magnesium element is 1-3%.

[0021] In a preferred embodiment, the calcium phosphate powder is tricalcium phosphate prepared by the following steps:

[0022] A first solution is prepared, wherein the first solution contains calcium ions; a phosphate solution is prepared, and the pH value is adjusted to 9.5-10.5 with an alkali solution to serve as a second solution;

[0023] The first solution and the second solution are heated and mixed, and reacted at 60-95° C. with stirring;

[0024] The suspension obtained after the reaction is centrifuged to obtain a precipitate, which is then washed and spray-dried to obtain a tricalcium phosphate powder material.

[0025] In a more preferred embodiment, the first solution further contains magnesium ions, and the molar ratio of calcium ions to magnesium ions in the first solution is 6-10; after the first solution and the second solution are mixed, the molar ratio of calcium ions to phosphate ions is 1.1-1.5; the calcium salt is selected from a combination of one or more of anhydrous calcium chloride, calcium chloride dihydrate and calcium nitrate tetrahydrate, the magnesium salt is selected from magnesium chloride hexahydrate and / or magnesium nitrate hexahydrate, the phosphate is selected from a combination of multiple of one of disodium hydrogen phosphate, diammonium hydrogen phosphate and sodium hydrogen phosphate, and the alkali solution is ammonia water or sodium hydroxide.

[0026] In some preferred embodiments, step B is specifically implemented as follows: add the second acid solution to the activated collagen sponge, and stir with a PTFE stirring paddle at 200-600 rpm for 1-10 minutes until it is completely dissolved; then add calcium phosphate powder and continue stirring for 5-30 minutes; finally, add a chemical crosslinking agent to the mixed slurry and stir for 1-5 minutes.

[0027] In some preferred embodiments, in step C, crosslinking is carried out in a constant temperature and humidity environment of -4-10°C for 0.5-4 hours, and then the mold is placed in a low-temperature storage cabinet at -40--10°C and frozen for 2-24 hours, and the initially formed composite material is demolded and taken out.

[0028] In some preferred embodiments, in step D, the composite material is immersed in a cross-linking agent solution for 6-48 hours, then the composite material is placed in pure water and stirred and cleaned at 200-600 rpm for 6-24 hours, and the composite material is freeze-dried; wherein the cross-linking agent includes a combination of one or more selected from genipin, glutaraldehyde and carbodiimide, with a concentration of 0.05-5%.

[0029] The present invention also adopts the following technical solution:

[0030] An artificial bone repair material is obtained by the above preparation method.

[0031] In some preferred embodiments, the porosity of the artificial bone repair material is 70-85%, and the mechanical strength is 0.2-1.0 MPa.

[0032] In some preferred embodiments, the relative density of the artificial bone repair material is 0.1 g / cm 3 More preferably, the relative density of the artificial bone repair material is 0.5 g / cm 3 above.

[0033] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0034] In the artificial bone repair body and preparation method of the present invention, the collagen raw material is activated, so that the solubility of collagen in the acidic solution is significantly improved; under heating or irradiation conditions, the acidic solution can increase the hydrophilic group content of the collagen raw material, thereby achieving the dissolution of more collagen molecules and improving the density of the artificial bone material after freeze-drying; the high-density collagen artificial bone repair material prepared by the present invention is 3-8 times higher than the density of the collagen sponge obtained by the conventional preparation method. Therefore, the compressive strength is significantly improved, which is more suitable for the requirements of the orthopedic implant environment; the high-density collagen artificial bone repair material prepared by the present invention is significantly higher than the collagen sponge obtained by the conventional preparation method, so the degradation time can be effectively extended after implantation into the human body, which can better match the growth rate of new bone. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solution of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0036] Figure 1 This is a photo of the artificial bone repair material prepared in Example 1.

[0037] Figure 2 This is a comparison chart of the compressive strength of the artificial bone repair materials prepared in Example 1 and Comparative Example 1.

[0038] Figure 3 These are photos of the osteogenesis effects of the artificial bone repair materials prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0039] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0040] The components of traditional bone repair materials are mainly a composite of collagen and hydroxyapatite powder, in which the hydroxyapatite content is about 55%. The process is to mix collagen powder and hydroxyapatite and then hot-press them at 90-130°C. The product has obvious deficiencies in degradation performance (hydroxyapatite is difficult to degrade in the body) and pore structure (hot-pressed molding is relatively dense).

[0041] Traditional bone repair material preparation technologies also include collagen / hydroxyapatite composite freeze-drying molding method and tricalcium phosphate ceramic surface perfusion collagen freeze-drying technology. Among them, the nano-scale hydroxyapatite powder used in the collagen / hydroxyapatite composite freeze-drying molding method has a content of 20-80%, which cannot achieve a higher ceramic phase content, and hydroxyapatite is difficult to degrade in the body. The main body of the tricalcium phosphate ceramic surface perfusion collagen freeze-drying technology is sintered calcium phosphate ceramics, which has insufficient matrix toughness and cannot achieve the unique shaping technology of collagen sponge.

[0042] The applicant has previously proposed an improved artificial bone repair material, which uses tricalcium phosphate powder as raw material, and a magnesium-containing tricalcium phosphate material with higher biological activity and full in vivo degradation is compounded with collagen molecules to form a new generation of highly biologically active and degradable artificial bone repair materials. However, in the scheme, the solubility concentration of bovine type I collagen in acid solution is difficult to exceed 10 mg / mL, which seriously restricts the density and mechanical strength of the collagen / tricalcium phosphate composite material.

[0043] The degradation time of collagen molecules in the body is generally short, and the degradation time of bovine type I collagen with a higher molecular weight (about 300kDa) is unlikely to exceed three months, while the regeneration and repair time of bone defects generally requires more than 6 months. Increasing the density of collagen sponge can effectively prolong the degradation time of collagen sponge, but the solubility of collagen materials is limited, and the solubility concentration of bovine type I collagen does not exceed 10mg / mL, resulting in low solid content of collagen after freeze-drying, making it difficult to increase density. Therefore, sponge-like artificial bone products formed using collagen composite calcium phosphate materials generally have a degradation time faster than the rate of new bone formation, making them difficult to use for filling and repairing bone defects. It is urgent to develop new high-density collagen artificial bone products.

[0044] On this basis, the inventor innovatively discovered a metastable state of collagen in the process of chemical cross-linking. In this state, free water inside collagen can be removed by extrusion, and the remaining bound water can be transformed and distributed in the collagen sponge to reshape the cross-linked network of the collagen sponge, so as to achieve the purpose of compression and densification of the sponge network structure. In this embodiment, the density of the artificial bone repair material is greatly improved by adding the pre-prepared surface-acidified calcium phosphate collagen composite powder to the mixed collagen solution, and the compressive strength of the material is significantly enhanced. Furthermore, compared with the traditional collagen compaction molding method, the high-strength collagen artificial bone repair material formed twice has a high degree of cross-linking, and the in vivo stability is greatly enhanced. Specifically, in this embodiment, the solubility of collagen in an acidic solution is significantly improved by activating the collagen raw material. Under heating or irradiation conditions, soaking in an acidic solution can increase the hydrophilic group content of the collagen raw material, thereby achieving the dissolution of more collagen molecules and improving the density of the artificial bone material after freeze-drying. The prepared high-density collagen artificial bone repair material is 3-8 times denser than the collagen sponge obtained by the conventional preparation method. Therefore, the degradation time can be effectively extended after implantation into the human body, which can better match the growth rate of new bone.

[0045] The preparation method of the artificial bone repair material of this embodiment is as follows:

[0046] (1) Weigh collagen and add it to a small amount of acid solution to fully soak it. Then heat the solution or sterilize it by irradiation so that the collagen molecules are fully activated and the solubility is significantly improved.

[0047] (2) Dissolve the activated collagen sponge in an acid solution to obtain a high-concentration collagen acid solution, add calcium phosphate powder, and add a chemical cross-linking agent after mixing evenly.

[0048] (3) The slurry is injected into the molding mold and slightly shaken until the liquid surface is flat. After low-temperature cross-linking, the mold is placed in a low-temperature storage cabinet for freezing, and then the preliminarily formed composite material is removed from the mold.

[0049] (4) Soaking the composite material in a chemical crosslinking agent solution to perform a second chemical crosslinking, placing the crosslinked composite material in pure water, stirring and washing, and then freeze-drying to obtain a high-density collagen artificial bone repair material.

[0050] Furthermore, the process of step (1) is specifically as follows: using an analytical balance to weigh the collagen and the acid solution, and immersing the entire collagen sponge in the solution. The solution is heated to 42-95 degrees or 8-45 kGy of Co 60 γ-ray irradiation, wherein the concentration of the acid solution is 0.2-10wt%, the mass ratio of collagen to the acid solution is 8-20%, and the solution heating time is 1-10 minutes.

[0051] The collagen used in step (1) includes but is not limited to type I collagen, type II collagen and recombinant collagen, etc., with a weight average molecular weight of 20,000-300,000 Da. The acid solution includes hydrochloric acid solution and / or acetic acid solution.

[0052] The process of step (2) is specifically as follows: add an acid solution to the activated collagen sponge, and stir for 1-10 minutes using a tetrafluoroethylene stirring paddle at 200-600rpm until completely dissolved. Add all the calcium phosphate powder to the collagen solution and continue stirring for 5-30 minutes. Finally, add a chemical crosslinking agent to the mixed slurry and stir for 1-5 minutes. Among them, the mass ratio of collagen to calcium phosphate powder is 0.05-1, the mass ratio of collagen to acid solution is 5-10%, the concentration of the acid solution is 0.2-10wt%, and the concentration of the chemical crosslinking agent is 10-500ppm.

[0053] The calcium phosphate powder used in step (2) includes but is not limited to tricalcium phosphate, magnesium-containing tricalcium phosphate, hydroxyapatite and octacalcium phosphate, etc. The acid solution includes hydrochloric acid solution and / or acetic acid solution, etc. The chemical cross-linking agent includes genipin and / or glutaraldehyde.

[0054] Preferably, the calcium phosphate powder is tricalcium phosphate powder containing or not containing magnesium. Specifically, the tricalcium phosphate powder material is prepared by the following steps:

[0055] (1) Dissolving a calcium salt and a magnesium salt in water to obtain a first solution, wherein the concentration of the calcium salt is 1-100 g / L, and the concentration of the magnesium salt is 0.4-40 g / L. Further, the molar ratio of calcium ions to magnesium ions is 6-10; the concentration of the calcium salt is more preferably 30-100 g / L, further 50-100 g / L, further 60-90 g / L, particularly 80-90 g / L; for example, 80 g / L, 82 g / L, 84 g / L, 86 g / L, 88 g / L or 90 g / L. Optionally, the concentration of the magnesium salt is more preferably 0.4-30 g / L, further 5-30 g / L, further 15-30 g / L, especially 20-30 g / L; for example 20 g / L, 22 g / L, 24 g / L, 25 g / L, 27 g / L or 29 g / L.

[0056] (2) dissolving phosphate in water, adjusting the pH to 9.5-10.5, further to 9.8-10.0 using alkaline solution (preferably ammonia water or sodium hydroxide), and obtaining a second solution, wherein the concentration of phosphate is 1-100 g / L. The concentration of phosphate in the second solution is more preferably 30-100 g / L, further 50-90 g / L, further 70-90 g / L, particularly 80-90 g / L; for example, 81 g / L, 83 g / L, 84 g / L, 85 g / L, 87 g / L or 88 g / L. More preferably, ammonia water is used to adjust the pH to 9.8-10.2. The inventors have found that the pH value has an important influence on the preparation of magnesium-containing tricalcium phosphate powder. According to the results of X-ray diffraction, a pH value that is too high or too low will produce more impurity phases, resulting in the obtained magnesium-containing tricalcium phosphate powder containing more calcium hydrogen phosphate impurity phases or hydroxyapatite.

[0057] (3) heating equal volumes of the first solution and the second solution to 60-95° C. and then mixing them, and performing a wet chemical reaction at 60-95° C. and normal pressure under stirring conditions, wherein the stirring rate is 100-500 rpm, and the molar ratio of calcium ions to phosphate ions is 1.1-1.5.

[0058] (4) The suspension after the wet chemical reaction is centrifuged to separate the precipitate, which is centrifugally washed with water for 4-8 times, the washed precipitate is added into 5-20 times the mass of water, stirred evenly to form a slurry, and the sizing agent is processed into tricalcium phosphate powder using a spray dryer, wherein the inlet air temperature of the spray dryer is 240-300° C., the outlet air temperature is 120-150° C., and the feed rate is 30-200 mL / min.

[0059] The calcium salt is selected from a combination of one or more of anhydrous calcium chloride, calcium chloride dihydrate and calcium nitrate tetrahydrate, the magnesium salt is selected from magnesium chloride hexahydrate and / or magnesium nitrate hexahydrate, and the phosphate is selected from a combination of multiple of one of disodium hydrogen phosphate, diammonium hydrogen phosphate and sodium hydrogen phosphate.

[0060] The specific content of magnesium in the tricalcium phosphate powder shows better biological activity and effectively promotes new bone formation. Compared with hydroxyapatite, the tricalcium phosphate powder material has better degradation performance, so it has significant advantages in the application of bone repair materials.

[0061] The process of step (3) is as follows: inject the mixed slurry into the mold, shake the mold to make the slurry liquid level flat, cross-link for 0.5-4 hours in a constant temperature and humidity environment of -4-10 degrees, then put the mold into a -40-10 degrees low temperature storage cabinet for 2-24 hours, and demold and take out the initially formed composite material.

[0062] The process of step (4) is specifically as follows: immersing the composite material in a chemical crosslinking agent solution for 6-48 hours, placing the crosslinked composite material in pure water for stirring and washing at 200-600 rpm for 6-24 hours, and freeze-drying the composite material to obtain a high-density collagen artificial bone repair material. The chemical crosslinking agent includes a combination of one or more selected from genipin, glutaraldehyde and carbodiimide, with a mass percentage of 0.05-5%.

[0063] The prepared high-density collagen artificial bone repair material has a porosity of 70-85%, a mechanical strength of 0.2-1.0Mpa, and a relative density of 0.1g / cm 3 More preferably 0.5 g / cm 3 above.

[0064] The magnesium-containing tricalcium phosphate powder used in the following examples and comparative examples was prepared by the following steps:

[0065] Weighing and dissolving: weigh 900 g of anhydrous calcium chloride and 270 g of magnesium chloride hexahydrate, dissolve in 10 L of water to obtain solution A; weigh 830 g of diammonium hydrogen phosphate, dissolve in 10 L of water, and use ammonia water to adjust the pH value of the solution to 10.0 to obtain solution B.

[0066] Heating and mixing: Heat solution A and solution B to 70°C and mix them, and continue stirring at 100 rpm to form a suspension.

[0067] Wet chemical reaction: The mixed suspension was heated and stirred at 70°C and 100 rpm for 12 hours.

[0068] Centrifugal washing: The suspension after the wet chemical reaction was centrifuged at 2000 rpm for 3 minutes to obtain the precipitate, and water was added and centrifuged for washing 5 times.

[0069] Spray drying: Add the washed precipitate to 10L of water and stir to form a slurry. Set the spray dryer inlet air temperature to 250°C and outlet air temperature to 120°C, spray dry the slurry at a rate of 50mL / min, and finally obtain tricalcium phosphate powder with a particle size distribution in the range of 1-20μm.

[0070] Example 1

[0071] Activation treatment: Use an analytical balance to weigh 0.5 g of bovine type I collagen and 2.5 g of 1 wt% acetic acid solution, squeeze the collagen sponge so that all materials are in contact with and immersed in the acetic acid solution, and heat to 45°C for 10 minutes.

[0072] Weighing and dissolving: Use an analytical balance to weigh 2.5 g of 1 wt % acetic acid solution, and add all of it to the activated solution. Use a tetrafluoroethylene stirring paddle to stir at 400 rpm for 10 minutes until it is completely dissolved.

[0073] Mixing configuration: Weigh 4.5 g of magnesium-containing tricalcium phosphate powder, add all of the magnesium-containing tricalcium phosphate powder to the collagen solution, and stir for 10 minutes using a tetrafluoroethylene stirring paddle at 400 rpm. Add 0.5 mL of 1 wt.% glutaraldehyde solution to the mixed solution, and stir for 1 minute using a tetrafluoroethylene stirring paddle at 400 rpm.

[0074] Injection molding: Inject the mixed slurry into the mold, shake the mold to make the slurry liquid level. Cross-link at -4 degrees for 1 hour, then put the mold into a -40℃ low-temperature storage cabinet for 4 hours, and demold and take out the initially formed composite material.

[0075] Cross-linking and cleaning: the composite material was immersed in a 1 wt.% glutaraldehyde solution for 6 hours, and then placed in pure water for cleaning at 400 rpm for 6 hours.

[0076] Freeze drying: The cleaned sample was placed in a -40°C refrigerator for 6 hours, and then freeze dried for 36 hours to finally obtain a high-density collagen artificial bone repair material (such as Figure 1 The relative density is 0.93 g / cm 3 .

[0077] Test: Compressive strength of high-density collagen artificial bone repair materials (such as Figure 2 The right side of the figure) and the New Zealand rabbit femoral condyle animal experiment (as shown in Figure 3 The results show that the high-density collagen artificial bone repair material has a significantly higher compressive strength than the control group (Comparative Example 1 below), and has an excellent bone formation effect after 3 months of implantation.

[0078] Example 2

[0079] Activation treatment: 1 g of bovine type I collagen and 4 g of 2 wt% acetic acid solution were weighed using an analytical balance, and the collagen sponge was squeezed so that all materials were in contact and immersed in the acetic acid solution. 25 kGy of Co 60 Gamma ray irradiation.

[0080] Weighing and dissolving: Use an analytical balance to weigh 4 g of 2 wt % acetic acid solution, and add all of it to the activated solution. Use a tetrafluoroethylene stirring paddle to stir at 400 rpm for 10 minutes until it is completely dissolved.

[0081] Mixing configuration: Weigh 5 g of magnesium-containing tricalcium phosphate powder, add all of the magnesium-containing tricalcium phosphate powder to the collagen solution, and stir for 10 minutes using a tetrafluoroethylene stirring paddle at 400 rpm. Add 1 mL of 1 wt.% glutaraldehyde solution to the mixed solution, and stir for 1 minute using a tetrafluoroethylene stirring paddle at 400 rpm.

[0082] Injection molding: Inject the mixed slurry into the mold, shake the mold to make the slurry liquid level. Cross-link at -4℃ for 2 hours, then put the mold into a -40℃ low-temperature storage cabinet for 6 hours, and demold and take out the initially formed composite material.

[0083] Cross-linking and cleaning: the composite material was immersed in a 1 wt.% glutaraldehyde solution for 6 hours, and then placed in pure water for cleaning at 400 rpm for 6 hours.

[0084] Freeze drying: The cleaned samples were placed in a -40℃ refrigerator for 6 hours, and then freeze dried for 36 hours to finally obtain a high-density collagen artificial bone repair material with a relative density of 0.62g / cm 3 .

[0085] Example 3

[0086] Activation treatment: 0.5 g of bovine type I collagen and 5.75 g of 0.2 wt% acetic acid solution were weighed using an analytical balance, and the collagen sponge was squeezed so that all materials were in contact with and immersed in the acetic acid solution, and heated to 50° C. for 2 minutes.

[0087] Weighing and dissolving: Use an analytical balance to weigh 2.5 g of 0.2 wt % acetic acid solution, and add all of it to the activated solution. Use a tetrafluoroethylene stirring paddle to stir at 400 rpm for 10 minutes until it is completely dissolved.

[0088] Mixing configuration: Weigh 10g of magnesium-containing tricalcium phosphate powder, add all of the magnesium-containing tricalcium phosphate powder to the collagen solution, and stir for 10 minutes using a tetrafluoroethylene stirring paddle at 400rpm. Add 0.5mL of 1wt.% glutaraldehyde solution to the mixed solution, and stir for 1 minute using a tetrafluoroethylene stirring paddle at 400rpm.

[0089] Injection molding: Inject the mixed slurry into the mold, shake the mold to make the slurry liquid level. Cross-link at -4℃ for 1 hour, then put the mold into a -40℃ low-temperature storage cabinet for 4 hours, and demold and take out the initially formed composite material.

[0090] Cross-linking and cleaning: the composite material was immersed in a 1 wt.% glutaraldehyde solution for 6 hours, and then placed in pure water for cleaning at 400 rpm for 6 hours.

[0091] Freeze drying: The cleaned samples were placed in a -40℃ refrigerator for 6 hours, and then freeze dried for 36 hours to obtain a high-density collagen artificial bone repair material with a relative density of 1.15 g / cm 3 .

[0092] Example 4

[0093] Activation treatment: Use an analytical balance to weigh 0.5 g of bovine type I collagen and 2 g of 10 wt% acetic acid solution, squeeze the collagen sponge so that all materials are in contact with and immersed in the acetic acid solution, and heat to 42°C for 5 minutes.

[0094] Weighing and dissolving: Use an analytical balance to weigh 2.5 g of 0.2 wt % acetic acid solution, and add all of it to the activated solution. Use a tetrafluoroethylene stirring paddle to stir at 400 rpm for 10 minutes until it is completely dissolved.

[0095] Mixing configuration: Weigh 0.5 g of magnesium-containing tricalcium phosphate powder, add all of the magnesium-containing tricalcium phosphate powder to the collagen solution, and stir at 400 rpm using a tetrafluoroethylene stirring paddle for 10 minutes. Add 0.5 mL of 1 wt.% glutaraldehyde solution to the mixed solution, and stir at 400 rpm using a tetrafluoroethylene stirring paddle for 1 minute.

[0096] Injection molding: Inject the mixed slurry into the mold, shake the mold to make the slurry liquid level. Cross-link at -4℃ for 1 hour, then put the mold into a -40℃ low-temperature storage cabinet for 4 hours, and demold and take out the initially formed composite material.

[0097] Cross-linking and cleaning: the composite material was immersed in a 1 wt.% glutaraldehyde solution for 6 hours, and then placed in pure water for cleaning at 400 rpm for 6 hours.

[0098] Freeze drying: The cleaned samples were placed in a -40°C refrigerator for 6 hours, and then freeze dried for 36 hours to obtain a high-density collagen artificial bone repair material with a relative density of 0.21 g / cm 3 .

[0099] Comparative Example 1

[0100] Weighing and dissolving: Use an analytical balance to weigh 0.5 g of bovine type I collagen sponge, 4.5 g of magnesium-containing tricalcium phosphate powder, and 40 g of 1 wt.% acetic acid solution. Add all the collagen sponge to the solution. Use a tetrafluoroethylene stirring paddle at 400 rpm to stir for 30 minutes.

[0101] Mixing configuration: Add all the magnesium-containing tricalcium phosphate powder to the collagen solution, and stir at 400 rpm using a tetrafluoroethylene stirring paddle for 10 minutes. Add 0.5 mL of 1 wt.% glutaraldehyde solution to the mixed solution, and stir at 400 rpm using a tetrafluoroethylene stirring paddle for 1 minute.

[0102] Injection molding: Inject the mixed slurry into the mold, shake the mold to make the slurry liquid level. Cross-link at -4℃ for 1 hour, then put the mold into a -40℃ low-temperature storage cabinet for 4 hours, and demold and take out the initially formed composite material.

[0103] Cross-linking and cleaning: the composite material was immersed in a 1 wt.% glutaraldehyde solution for 6 hours, and then placed in pure water for cleaning at 400 rpm for 6 hours.

[0104] Freeze drying: The cleaned samples were placed in a -40°C refrigerator for 6 hours, and then freeze dried for 36 hours to obtain a high-density collagen artificial bone repair material with a relative density of 0.075 g / cm 3 .

[0105] Test: Compare the compressive strength of collagen artificial bone repair materials (such as Figure 2 left) and New Zealand rabbit femoral condyle animal experiments (as shown in Figure 3 The results of animal experiments show that collagen artificial bone repair materials with lower density degrade faster and have poor bone formation effect.

[0106] Comparative Example 2

[0107] Activation treatment: 0.5 g of bovine type I collagen and 2.5 g of 1 wt% acetic acid solution were weighed using an analytical balance, and the collagen sponge was squeezed so that all materials were in contact with and immersed in the acetic acid solution, and heated to 37° C. for 10 minutes.

[0108] Weighing and dissolving: Use an analytical balance to weigh 2.5g of 1wt% acetic acid solution and add it all to the activated solution. Use a PTFE stirring paddle at 400rpm for 30 minutes to stir if it still cannot be completely dissolved. Continue to add 40g of 1wt% acetic acid solution to fully dissolve it.

[0109] Mixing configuration: Weigh 4.5 g of magnesium-containing tricalcium phosphate powder, add all of the magnesium-containing tricalcium phosphate powder to the collagen solution, and stir for 10 minutes using a tetrafluoroethylene stirring paddle at 400 rpm. Add 0.5 mL of 1 wt.% glutaraldehyde solution to the mixed solution, and stir for 1 minute using a tetrafluoroethylene stirring paddle at 400 rpm.

[0110] Injection molding: Inject the mixed slurry into the mold, shake the mold to make the slurry liquid level. Cross-link at -4℃ for 1 hour, then put the mold into a -40℃ low-temperature storage cabinet for 4 hours, and demold and take out the initially formed composite material.

[0111] Cross-linking and cleaning: the composite material was immersed in a 1 wt.% glutaraldehyde solution for 6 hours, and then placed in pure water for cleaning at 400 rpm for 6 hours.

[0112] Freeze drying: The cleaned samples were placed in a -40℃ refrigerator for 6 hours, and then freeze dried for 36 hours to obtain a high-density collagen artificial bone repair material with a relative density of 0.08g / cm 3 .

[0113] In summary, the collagen raw material is activated in the embodiment, combined with the secondary molding process, and the acid solution immersion under heating and irradiation conditions can increase the hydrophilic group content of the collagen raw material, thereby achieving the dissolution of more collagen molecules and improving the density of the artificial bone material after freeze-drying. Compared with the control group of the traditional slurry compaction molding method, the two cross-linking molding method of the embodiment (steps (3) and (4)) is also significantly beneficial to improve the cross-linking degree of the bone repair material, and the stability of the bone repair material implanted in the human body is greatly enhanced.

[0114] As shown in this specification and claims, the terms "comprises" and "include" only indicate the inclusion of the steps and elements that have been clearly identified, and these steps and elements do not constitute an exclusive list, and the method or device may also include other steps or elements. The term "and / or" as used herein includes any combination of one or more of the relevant listed items.

[0115] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0116] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art. If there is any conflict or inconsistency between the definitions used herein and the definitions contained in other public documents, the definitions used herein shall prevail.

[0117] The above embodiment is only for illustrating the technical concept and features of the present invention, and is a preferred embodiment. Its purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and it cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an artificial bone repair material, characterized in that: include: A. obtaining a mixture of collagen and a first acid solution, and heating or irradiating the mixture to activate collagen molecules; B. dissolving the activated collagen in the second acid solution to obtain a collagen acid solution, adding calcium phosphate powder, mixing evenly, and then adding a cross-linking agent to obtain a slurry; C. Injecting the slurry into a mold, undergoing cross-linking reaction, and demoulding.

2. The preparation method according to claim 1, characterized in that: In step A, the mixed solution is heated to 40-95° C. for activation, or the mixed solution is irradiated with gamma rays for activation.

3. The preparation method according to claim 1 or 2, characterized in that: In step A, the concentration of the first acid solution is 0.2-10wt%, the first acid solution includes a hydrochloric acid solution or an acetic acid solution, the mass percentage of collagen in the mixed solution is 8-20%, the heating activation time is 1-10 minutes; the irradiation is 8-45kGy Co 60 Gamma ray irradiation.

4. The preparation method according to claim 1, characterized in that: The collagen includes one or more selected from type I collagen, type II collagen and repeated collagen, and the weight average molecular weight of the collagen is 20000-300000 Da.

5. The preparation method according to claim 1, characterized in that: In step B, the mass ratio of collagen to calcium phosphate powder is 0.05-1, the mass percentage of activated collagen in the collagen acid solution is 5-10%, and the concentration of the cross-linking agent is 10-500 ppm.

6. The preparation method according to claim 1 or 5, characterized in that: In step B, the concentration of the second acid solution is 0.2-10wt%, and the second acid solution includes a hydrochloric acid solution or an acetic acid solution; the calcium phosphate powder includes a combination of one or more selected from tricalcium phosphate, magnesium-containing tricalcium phosphate, hydroxyapatite and octacalcium phosphate; and the cross-linking agent includes genipin and / or glutaraldehyde.

7. The preparation method according to claim 1 or 5, characterized in that: Step B is specifically implemented as follows: add the second acid solution to the activated collagen sponge, and stir with a PTFE stirring paddle at 200-600 rpm for 1-10 minutes until it is completely dissolved; then add calcium phosphate powder and continue stirring for 5-30 minutes; finally, add a chemical crosslinking agent to the mixed slurry and stir for 1-5 minutes.

8. The preparation method according to claim 1, characterized in that: In step C, cross-linking is carried out in a constant temperature and humidity environment of -4-10°C for 0.5-4 hours, and then the mold is placed in a low-temperature storage cabinet at -40-10°C and frozen for 2-24 hours, and the initially formed composite material is removed from the mold.

9. The preparation method according to claim 1, characterized in that: The preparation method further comprises the following step D: immersing the initially formed composite material removed from the mold in step C into a crosslinking agent solution for secondary chemical crosslinking, washing the crosslinked composite material, and drying and forming the composite material to obtain an artificial bone repair material.

10. The preparation method according to claim 9, characterized in that: In step D, the composite material is immersed in a crosslinker solution for 6-48 hours, then the composite material is placed in pure water and stirred and washed at 200-600 rpm for 6-24 hours, and the composite material is freeze-dried; wherein the crosslinker includes a combination of one or more selected from genipin, glutaraldehyde and carbodiimide, with a concentration of 0.05-5%.

11. An artificial bone repair material, characterized in that: The artificial bone repair material is obtained by the preparation method according to any one of claims 1 to 10, wherein the porosity of the artificial bone repair material is 70-85% and the mechanical strength is 0.2-1.0 MPa.